A creative geometric investigation in Middle School: the case of quadrilaterals - Silva, Cristian Martins da; Kiefer, Juliana Gabriele; Leivas, José Carlos Pinto (Educação Matemática Debate, 2025)
The research aimed to analyze the mathematical creativity of students in Middle School in the production of different quadrilaterals in 3×3 grids, considering the fluency, flexibility and originality of the answers. Characterized as a qualitative approach research, it was observed that, in the answers of 12 students, although some showed the ability to generate varied solutions, there were difficulties in recognizing and using geometric transformations, such as rotations, reflections and translations. These results reveal the need for methodologies that encourage creativity and geometric thinking, for a deeper and more versatile learning. The research contributes to the debate on creativity in school Mathematics, fostering pedagogical practices that promote autonomy and critical thinking in the development of geometric skills and problem solving.